2022
DOI: 10.1093/nargab/lqac087
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive comparison of gene expression diversity among a variety of human stem cells

Abstract: Several factors, including tissue origins and culture conditions, affect the gene expression of undifferentiated stem cells. However, understanding the basic identity across different stem cells has not been pursued well despite its importance in stem cell biology. Thus, we aimed to rank the relative importance of multiple factors to gene expression profile among undifferentiated human stem cells by analyzing publicly available RNA-seq datasets. We first conducted batch effect correction to avoid undefined var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
1
2
0
Order By: Relevance
“…Interestingly, reserve respiratory capacity was higher in untreated HF2303 relative to HF2927 cells, and higher in SDC compared to CSCs (S3_Fig). Replication-dependent histones were highly enriched in HF2303 CSCs, in the absence of enrichment in cell proliferation markers (Fig 7, A in S2 Table ), as previously observed for embryonic and induced pluripotent stem cells [59]. Several nuclear pseudogenes with sequence similarity to mitochondrially encoded 16S rRNA (e.g.…”
Section: Transcriptional Reprogramming In Response To Csc Differentia...supporting
confidence: 77%
“…Interestingly, reserve respiratory capacity was higher in untreated HF2303 relative to HF2927 cells, and higher in SDC compared to CSCs (S3_Fig). Replication-dependent histones were highly enriched in HF2303 CSCs, in the absence of enrichment in cell proliferation markers (Fig 7, A in S2 Table ), as previously observed for embryonic and induced pluripotent stem cells [59]. Several nuclear pseudogenes with sequence similarity to mitochondrially encoded 16S rRNA (e.g.…”
Section: Transcriptional Reprogramming In Response To Csc Differentia...supporting
confidence: 77%
“…Although 10 different H3 genes encode the same H3.1 amino acid sequence, a recent study reported that only the HIST1H3H and HIST1H3D genes were differentially regulated in metastatic breast cancer [ 139 ]. This suggests that at the transcript level, these histone genes may not be functionally redundant [ 140 , 141 ]. HIST3H3 is also upregulated in breast cancer and is positively associated with activated polymorphonuclear neutrophil (PMN)-induced breast cancer metastasis [ 142 ].…”
Section: Dysregulated Histone Genes In Breast Cancermentioning
confidence: 99%
“…Unlike MSCs, iPSCs and ESCs possess greater pluripotency, enabling the generation of a broader range of cell types. However, this approach is associated with increased ethical concerns for ESCs and increased tumorigenic potential for both iPSCs and ESCs ( 18 , 19 ). Compared to their broader differentiation capabilities, the unique advantages of MSCs in regenerative medicine, particularly in mitigating autoimmune responses in diabetes, are the heightened risks associated with iPSCs and ESCs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the exploration of MSC-derived exosomes represents an advancement in therapeutic strategies for pancreatic islet transplantation, highlighting a new direction in MSC-based treatments (17). These exosomes, as carriers of regenerative and immunomodulatory factors, present a novel approach to enhancing the microenvironment of transplanted islets, potentially reducing immunological rejection and supporting islet cell survival and function.…”
Section: Introductionmentioning
confidence: 99%